Employing longest common subsequence method to retrieve translated Al-Quran documents / Muhamad Shamsudin - Shamsudin, Muhamad (2001)
Dynamic programming is introduced to serve as underlying principle for solving problems in different areas such as operations research, computer science, speech processing and string processing. Longest Common Subsequence algorithm (LCS) has been developed to solve string matching problems. This method is employed to retrieve documents from the translated Al-Quran. This approach will be introduced in the Web page as a search engine. Search engine will collate and return a list of clickable URLs containing presentations that match with word related. The list is ordered, with the best match appearing at the top of the Web page.